Pre-anesthetic use of butorphanol for the prevention of emergence agitation in thoracic surgery: A multicenter, randomized controlled trial - Meng, Tao; Lin, Xiaowen; Li, Ximing; Yue, Fangli; Zhang, Yuzhu; Wang, Yingbin; Gu, Jianhua; Yang, Zaiqi; Yu, Hongli; Lv, Kun; Liang, Shengyong; Li, Xingda; et al. (Frontiers in Medicine, 2022)
Background: Emergence agitation (EA) is common in patients after general anesthesia (GA) and is associated with poor outcomes. Patients with thoracic surgery have a higher incidence of EA compared with other surgery. This study aimed to investigate the impact of preanesthetic butorphanol infusion on the incidence of EA in patients undergoing thoracic surgery with GA. Method: This prospective randomized controlled trial (RCT) was conducted in 20 tertiary hospitals in China. A total of 668 patients undergoing elective video-assisted thoracoscopic lobectomy/segmentectomy for lung cancer were assessed for eligibility, and 620 patients were enrolled. 296 patients who received butorphanol and 306 control patients were included in the intention-to-treat analysis. Patients in the intervention group received butorphanol 0.02mg/kg 15 min before induction of anesthesia. Patients in the control group received volume-matched normal saline in the same schedule. The primary outcome was the incidence of EA after 5 min of extubation and EA was evaluated by Riker Sedation-Agitation Scale (RSAS). Results: In total, 296 patients who received butorphanol and 306 control patients were included in the intention-to-treat analysis. The incidence of EA 5 min after extubation was lower with butorphanol treatment: 9.8% (29 of 296) versus 24.5% (75 of 306) in the control group (P = 0.0001). Patients who received butorphanol had a lower incidence of drug-related complications (including injecting propofol pain and coughing with sufentanil): 112 of 296 versus 199 of 306 in the control group (P = 0.001) and 3 of 296 versus 35 of 306 in the control group (P = 0.0001). NRS scores at radial artery placed, 5 min after extubation and 15 min after arrival at PACU were statistically significantly lower for butorphanol group compared to control group. Conclusion: Preanesthetic administration of butorphanol reduced the incidence of EA after thoracic surgery under GA. Trial registration: ChiCTR1900025705.